La epistemología constructivista en el contexto de la post-modernidad - Camejo, Armando J. (Nómadas. Critical Journal of Social and Juridical Sciences, 2006)
The present work approaches us to the discussion of the term constructivismo in the environment epistemologist, to its theoretical derivations and the application in the contexts of the knowledge. It is a boarding whose profile of I dialogue sample a reference on the vision of the constructivism in the contemporary social postmodern space. In this sense, emphasis is made to the possibility that this argument on the constructivism becomes an alternative epistemological for the social sciences leaving of a contextual revision of the term, as well as of its theoretical-methodological arguments.